The relationship between field independence and lucid dreaming ability - Gackenbach, Jayne; Heilman, Nancy; Boyt, Sheila; LaBerge, Stephen (My University, 1985)
It was hypothesized that field independence would be more characteristic of individuals who are able to recognize that they are dreaming while still in the dream (i.e., "lucid dreamers"), than of those who do not possess this ability. In three studies the measures of field independence utilized were: Group Embedded Figures Test, Embedded Figures Test and Portable Rod-and-Frame Test. The hypothesis was strongly supported for men and partially supported for women.
Keywords: males; females; dreams